Sweet Potato Value Chain Analysis Reveals Opportunities for Increased Income and Food Security in Northern Ghana. (2nd November 2017) - Sugri, Issah; Maalekuu, Bonaventure Kissinger; Gaveh, Eli; Kusi, Francis
Abstract : Sweet potato has gained prominence due to its ability to adapt to wide production ecologies and yield response to minimal external inputs. Orange-fleshed cultivars in particular have immense potential to improve household income and nutrition in sub-Saharan Africa. However, the sweet potato value chain (SPVC) is not well-developed in many producing countries. The study was conducted in two regions to characterize the production operations as well as identify opportunities to propel the SPVC in Northern Ghana. Data were collected using mixed methods including structured questionnaires via face-to-face interviews. Analysis of strengths, weaknesses, opportunities, and threats (SWOT) was conducted at multistakeholder platforms with different actors. Gross margin profit and benefit-cost ratios were determined by using six cost variables. Overall, the industry was largely a fresh produce market, targeting food vendors, processors, and direct selling to wholesalers, retailers, and household consumers. The SWOT analysis revealed wide-ranging opportunities including favourable production ecologies, processing options, and insatiable local and international markets. The institutional actors need to network the primary actors to synergistically operate with a collective profit motive. The most prioritized production constraints such as access to seed, cost of chemical fertilizer, short shelf-life, field pests and diseases, and declining soil fertility should be addressed.